Adrenal Insufficiency under Standard Dosage of Glucocorticoid Replacement after Unilateral Adrenalectomy for Cushing's Syndrome. (7th June 2016) - Fujii, Kentaro; Miyashita, Kazutoshi; Kurihara, Isao; Hiratsuka, Ken; Sato, Seiji; Yokota, Kenichi; Kobayashi, Sakiko; Shibata, Hirotaka; Itoh, Hiroshi
Abstract : Glucocorticoid replacement is needed for patients after adrenal surgery for Cushing's syndrome; however, the adequate dosage is not easily determined. The patient was a 62-year-old woman who has had hypertension for 5 years and presented with heart failure due to hypertrophic cardiomyopathy. She consulted with us because of general fatigue, facial edema, and muscle weakness and was diagnosed with Cushing's syndrome. A laparoscopic left adrenalectomy was performed, standard dosage of postoperative replacement was administered, and she was discharged with 30 mg/day of hydrocortisone (cortisol). However, she suffered from loss of appetite and was transferred to an emergency unit with the symptoms of adrenal insufficiency on postoperative day 15. After initial hydrocortisone replacement with 200 mg/day, the dosage was gradually decreased during hospitalization; however, reduction of hydrocortisone dosage lower than 60 mg/day was difficult because of nausea and fatigue. Her circadian cortisol profile after hydrocortisone administration showed delayed and lowered peaks, which suggested that hydrocortisone absorption in the intestine was impaired. Therefore, complicated heart failure may have led to the adrenal insufficiency in the patient. In such cases, we should consider postoperative administration of more than the standard dosage of hydrocortisone to avoid adrenal insufficiency after surgery for Cushing's syndrome.